Microbial community dynamics in an anaerobic biofilm reactor treating heavy oil refinery wastewater. Issue 109 (10th November 2016) - Dong, Honghong; Dong, Hao; Zhang, Zhongzhi; Sun, Shanshan; Wang, Wei; Ke, Ming; Song, Zhaozheng; Zhang, Zhenjia; Wang, Jianfeng; Wu, Wei-Min
Abstract : We have established an anaerobic biofilm reactor (AnBR) for treating heavy oil refinery wastewater at the field scale for the first time. Abstract : We have established an anaerobic biofilm reactor (AnBR) for treating heavy oil refinery wastewater at the field scale for the first time. The AnBR showed a good performance with a chemical oxygen demand (COD) removal efficiency of 60% after 11 days at a Hydraulic Retention Time (HRT) of 72 h. A relatively stable performance was maintained for 79 days at 35 ± 1 °C when the HRT was shortened to 60 h (the average removal efficiency of COD increased to 80.42%). The diversity and dynamics of microbial communities were investigated in detail. A total of 797 732 high-quality sequences were obtained after trimming, assembling paired-end reads, and quality screening of raw reads by Illumina MiSeq sequencing of the two bacterial 16S hypervariable regions V3 and V4. The results showed that the biofilm bacterial species diversity increased from the start-up stage to steady-state stage, whereas the diversity of the archaeal species of the biofilm decreased. During steady state, biofilm collected from the middle of the AnBR was dominant bacterial genera, Acinetobacter and Pseudomonas, that played a vital role in hydrocarbon-degradation. Methanosaeta, which is regarded as a major acetoclastic methanogen, was the predominant archaeal genus from the same biofilm location. The results of rapid start-up (11 days) and high COD removal efficiency (80.42%) of the AnBR were attributed to the highly efficient biofilm. This study demonstrated the potential application of the AnBR as an alternative for high-efficiency anaerobic treatment of heavy oil refinery wastewater.